Impact of Digital Iqro Qur’anic Learning on Emotional Regulation of Dyslexic Elementary Students in Banten (International Journal of Education and Literature, 2025)
This study investigates the impact of Al-Quran learning strategies using Digital Iqro on the emotional regulation of dyslexic elementary students in Banten. Employing a quasi-experimental design with a quantitative approach, the research involved 100 purposively selected participants. Data were collected via questionnaires and analyzed using SPSS. Findings revealed that in the conventional learning group, the direct Al-Quran learning strategy influenced emotional regulation by 31%, while the indirect strategy had a 40% influence. In contrast, for the digital learning group, the direct strategy showed a moderate impact of 14%, and the indirect strategy showed no measurable effect (0%) on emotional regulation.These results suggest that while conventional methods may have stronger effects, digital strategies still offer moderate benefits and potential. The study contributes valuable insights for educators and policymakers in the context of advancing education within the Society 5.0 era.